Enhancing nutritional knowledge and self-regulation among adolescents: efficacy of a multifaceted food literacy intervention - Mancone, Stefania; Corrado, Stefano; Tosti, Beatrice; Spica, Giuseppe; Di Siena, Francesco; Misiti, Francesco; Diotaiuti, Pierluigi (Frontiers in Psychology, 2024)
This health literacy intervention study, conducted on adolescent students, aimed to evaluate the impact of a comprehensive educational program on promoting healthy eating habits. The intervention sought to enhance adolescents’ knowledge about nutrition, foster self-regulation skills, and ultimately improve their overall health, including their body mass index (BMI). Through a multi-component approach that combined theoretical learning with practical activities and the integration of digital tools such as the MyFitnessPal app, the study targeted improvements in food literacy, which encompasses nutrition knowledge, food label interpretation skills, and cooking abilities. These elements are critical in influencing adolescents’ food choices and eating behaviors, with a focus on increasing the consumption of fruits and vegetables while reducing the intake of fast food and processed snacks. The intervention was structured around a series of educational workshops and interactive sessions, facilitated by professionals experienced in nutrition. These sessions covered topics such as food composition, the importance of a balanced diet, and strategies for avoiding excessive consumption of processed and high-energy-density foods. A distinctive feature of the program was its use of digital tools to enhance engagement and allow for the practical application of learned concepts through food tracking and activity monitoring. Preliminary results indicate positive outcomes in terms of increased food knowledge and improved dietary habits among participants. Notably, there was a significant improvement in adolescents’ BMI, highlighting the potential of food literacy interventions to contribute to better physical health outcomes. The study underscores the importance of adopting multidisciplinary and technology-enhanced approaches in educational programs aimed at promoting healthy eating among adolescents. The study’s findings suggest that well-structured food education programs, tailored to address the specific needs of adolescents, can facilitate positive changes in eating behavior. This highlights the critical role of food literacy in adolescents’ health and wellbeing and points to the need for continued investment in research and development to optimize intervention strategies. The integration of digital technologies and a focus on self-regulation strategies are identified as promising avenues for future research and educational practice, reinforcing the call for innovative investments in food education and health promotion among the youth.